PC.90 Neonatal Bartters Syndrome – a rare cause of polyhydramnios and premature birth. (9th June 2014) - Soni, R; Ali, H; Fitzpatrick, M
Abstract : A baby boy was born at 31 weeks gestation via caesarean section following premature rupture of membranes and poor CTG. The pregnancy had been complicated by severe polyhydramnios from 24 weeks of gestation. Amnio-drainage was undertaken at 27 weeks followed by a course of Sulindac (NSAID, Non steroidal anti inflammatory drug) at 29 weeks of gestation with subsequent improvement in the amniotic fluid index. Over the first few days of life, the baby developed a gradual deterioration of renal function, polyuria, hyponatraemia and failure to thrive. The initial clinical picture was nonspecific and attributed to prematurity. The renal function subsequently improved but he progressively became hypokalaemic and alkalotic. At 3–4 weeks of age, due to persistent tubulopathy, the diagnosis of Bartter's syndrome was suspected. This was supported by findings of high renin and aldosterone levels. Neonatal Bartters is rare. It is characterised by foetal polyuria and polyhydramnios, premature birth, postnatal episodes of severe dehydration, growth retardation, hypercalciuria and early nephrocalcinosis. It is the result of mutation of a gene responsible for renal tubular Na-K-2Cl co-transport or another gene, which controls the ATP-dependant potassium channel. There is evidence that NSAIDs have a role in decreasing amniotic fluid production and prevent/delay premature birth. Their effects on renal function of the fetus and neonate requires further research and an atypical presentation of Neonatal Bartters can be expected in the neonatal period. Amniotic fluid analysis to rule out Bartters should be considered when contemplating the use of NSAIDs in such cases.